Analysis of Factors Affecting Tourists’ Visiting Decision on Tourist Destinations in Lampung Province - Novita Sari; Firmansyah Yunialfi Alfian; Muhammad Dwiyan Aditya (Proceeding International Conference on Information Technology and Business, 2021)
Lampung was one of the provinces in Indonesia that had great natural, cultural developed tourist attraction potentials. These potentials were seen on beautiful natural panoramas and geographical features including seas, rivers, hills, and mountains that had their own uniqueness and characteristics. Moreover, the diverse cultures and customs were also unique and different from the other provinces inIndonesia. With these conditions, Lampung was able to be developed as a tourist destination, particularly its location that was also very close to the Java Island and the other cities of Sumatra Island. Some of the natural and cultural beauty in Lampung had been developed and successfully became a tourist destination. Tourism spots commercialized in Lampung included beaches and seas with high waves, traditional customs, mountainous nature, forests, rivers with diving and fishing facilities and the other potentials. The problem of this research was the decreasing number of tourists visiting the tourist destinations in Lampung Province. The objective of this research was determining the factors affect ing the tourists’ visit ing decision on the tourist destinations in Lampung Province. In this research, aresearch model was developed with seven hypotheses that had been formulated. The number of sample of this research was 110 respondents as tourists visiting the tourist destinations in Lampung Province. The method of this research was the PLS-SEM method. The result of this research showed that the the Advertising, the servicequality, and the tourist attraction had a significant effect on the tourists’ visit ing decision; moreover, the variables that had a significant effect on the tourism image were the Advertising and the service quality. In addition, the variable affecting the tourist attraction was also the service quality. Keywords—Service Quality, Visiting Decision, Tourism Image, Advertising, Tourist Attraction